Safety and Efficacy of Placenta-Derived Mesenchymal Stem Cell Treatment for Diabetic Patients with Critical Limb Ischemia: A Pilot Study - Wang, Jiao; Zeng, Xiang-Xia; Cai, Wei; Han, Zhi-Bo; Zhu, Ling-Yan; Liu, Jian-Ying; Xu, Ji-Xiong (Experimental and Clinical Endocrinology & Diabetes, 2019)
Aim Diabetic foot has become the main cause of non-traumatic amputation. Stem cell therapy, especially mesenchymal stem cells (MSCs), holds a great promise as a therapy for diabetic foot with ischemia limb arterial disease. The aim of this pilot study is to evaluate the safety and efficacy of placenta-derived MSCs (P-MSCs) treatment for diabetic patients with critical limb ischemia (CLI).Methods Four eligible diabetic patients with CLI were consecutively enrolled in this pilot study. On the base of the standard-of-care treatment, these patients accepted P-MSCs treatment by intramuscular injection for successive 3 times at an interval of 4 weeks, and the safety and efficacy of placenta-derived MSCs (P-MSCs) treatment were evaluated.Results There were no serious adverse events during the period of P-MSCs injection and the 24-weeks follow-up period. The clinical ischemic features of patients were improved 24 weeks after P-MSCs treatment. The scores of resting pain and limb coldness significantly decreased, and pain-free walking distance significantly increased from baseline to 24 weeks after P-MSCs therapy. The resting ankle brachial index increased, but no statistically significant difference was found. The findings of magnetic resonance angiography showed the increase of collateral vessel formation in one patient, but there were no significant changes observed in the other patients.Conclusions The data in this pilot study indicated that multiple intramuscular P-MSCs injections may be a safe and effective alternative therapy for diabetic patients with CLI, and larger, placebo-controlled, perspective studies are needed to prove these results.
Keywords: critical limb ischemia; diabetic foot; placenta-derived mesenchymal stem cell; cell therapy